Prognostic value of risk stratification using blood parameters for nivolumab in Japanese patients with metastatic renal-cell carcinoma. (22nd November 2019) - Yamamoto, Yoshiaki; Matsuyama, Hideyasu; Matsumoto, Hiroaki; Sakano, Shigeru; Fuji, Nakanori; Oba, Kazuo; Yamamoto, Mitsutaka; Kamiryo, Yoriaki; Hiragino, Takeshi; Nagao, Kazuhiro; Takai, Kimio; Aoki, Akihiko
Abstract: Background: Nivolumab is a standard treatment for previously treated advanced renal-cell carcinoma. However, nivolumab is effective in only a limited number of patients; therefore, we evaluated the prognostic value of several biomarkers, including inflammation-based prognostic scores and changes in these scores following nivolumab treatment in Japanese patients with metastatic renal-cell carcinoma. Methods: We retrospectively reviewed the medical records of 65 patients with previously treated metastatic renal-cell carcinoma and who received nivolumab. Inflammation-based prognostic scores, including neutrophil/lymphocyte ratio, platelet/lymphocyte ratio, lymphocyte/monocyte ratio, and Glasgow prognostic score before and 6 weeks after the treatment were recorded. Categorical variables influencing disease-specific survival were compared using Cox proportional-hazards regression models. Results: Univariate analysis showed that Memorial Sloan-Kettering Cancer Center risk score ( P = 0.0052), lactate dehydrogenase ( P = 0.0266), lymphocyte/monocyte ratio ( P = 0.0113), and platelet/lymphocyte ratio ( P = 0.0017) had a significant effect on disease-specific survival. Multivariate analyses showed that platelet/lymphocyte ratio and lactate dehydrogenase were found to be independent prognostic factors for disease-specific survival ( P = 0.0008, risk ratio (RR) = 7.95, 95% confidence interval, 2.16–51.64 and P = 0.0123, RR = 3.92, 95% confidence interval, 1.37–10.80, respectively). The combination of platelet/lymphocyte ratio and lactate dehydrogenase was the most significant prognostic biomarker in metastatic renal-cell carcinoma ( P < 0.0001). Changes in lymphocyte/monocyte ratio and platelet/lymphocyte ratio in response to nivolumab were significant prognostic factors for disease-specific survival ( P < 0.0001 and P = 0.0477, respectively). Conclusions: The combination of platelet/lymphocyte ratio and lactate dehydrogenase may be a potential biomarker for estimating disease-specific survival in Japanese patients with metastatic renal-cell carcinoma treated by nivolumab. Abstract : We evaluated the prognostic value of biomarkers in nivolumab treated Japanese patients with metastatic renal-cell carcinoma. The combination of platelet/lymphocyte ratio and lactate dehydrogenase was the most significant prognostic biomarker.